Makanan Tradisional Mangut Beong sebagai Daya Tarik Wisata Gastronomi di Kabupaten Magelang Jawa Tengah - Hardyanti Hardyanti; Nuzulul Faidatun (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The city of Magelang has a variety of scattered tourist destinations, various tourist attractions that are quite high, namely historical tourism. In addition to being famous for historical tourism, there is a need for new attractive tourist destinations and in general to encourage Regional Original Income (PAD), namely with the potential and opportunities for developing Traditional Food tourism. Traditional Food Tourism in Magelang City is now a tourist icon because there are types of tourists who come to a destination to enjoy the food. The food that became the icon is mangut beong which is quite famous among tourists. Traditional Food Tourism is if tourists who come to a tourist destination aim to enjoy traditional food, but if tourists come to a destination to participate in the preparation and presentation process, it is known as gastronomic tourism. The traditional food of mangut beong has not received the government's attention to help manage it as an icon of the city of Magelang and as a potential for gastronomic tourism. The purpose of this study was to determine the gastronomic component of mangut beong traditional food in the city of Magelang, the potential to be used as a gastronomic tourist attraction and the role of stakeholders based on creative reunurship of Miss Helix Wisata. This research method is a mixed method with a descriptive analysis method approach. in-depth interviews, observations and documentation. The results of the study are to describe the 9 gastronomic components containing the history & philosophy of the meaning of the name